The formation of a European identity in jeopardy? - The impact of Turkish European Union accession negotiations - Shine, Declan (My University, 2009)
Abstract The following research report will look at efforts that have been made by EU elites to forge a European identity since its inception. In this light, this research report will evaluate whether there has been steady support for a European identity among EU elites and EU citizens in the different EU member states and thus assess whether the possible accession of Turkey into the EU, a Muslim country, has jeopardised its formation. This research study will be explained by investigating various theoretical traditions on how national identities emerge within the nation-state model and show that Constitutional Patriotism is the approach that EU elites have decided to take in identity formation at the EU level.